Feeding behavior of growing-finishing pigs reared under precision feeding strategies - Andretta, I. (2016)
The feeding behavior of growing-finishing pigs reared under precision feeding strategies was studied in 35 barrows and 35 females (average initial BW of 30.4 +/- 2.2 kg) over 84 d. Five different feeding programs were evaluated, namely a conventional 3-phase program in which pigs were fed with a constant blend of diet A (high nutrient density) and diet B (low nutrient density) and 4 daily phase-feeding programs in which pigs were fed daily with a blend meeting 110, 100, 90, or 80% of the individual Lys requirements. Electronic feeder systems automatically recorded the visits to the feeder, the time of the meals, and the amount of feed consumed per meal. The trial lasted 84 d and the database contained 59,701 feeder visits. The recorded database was used to calculate the number of meals per day, feeding time per meal (min), intervals between meals (min), feed intake per meal (g), and feed consumption rate (feed intake divided by feeding time per meal, expressed in g/min) of each animal. The feeding pattern was predominantly diurnal (73% of the feeder visits). Number of meals, duration of meals, time between meals, feed consumed per meal, and feed consumption rate were not affected by the feeding programs. The females ingested 19% less feed per meal and had a 6% lower feed consumption rate in comparison with the barrows (P < 0.05). Pig feeding behavior was not correlated with diet composition. However, feed efficiency was negatively correlated with amount of feed consumed per meal (r = -0.38, P < 0.05) and feed consumption rate (r = -0.44, P < 0.05). Feed consumption rate was also negatively correlated with protein efficiency (r = -0.44, P < 0.05). Multivariate analysis indicated that feed consumption rate and number of meals per day are the variables related most closely to pig production performance results. Current results indicate that using precision feeding as an approach to reduce Lys intake does not interfere with the feeding behavior of growing-finishing pigs.